Application of Mediation Obligations at the Level of Appeal and Cassation Legal Remedies in Indonesia - Gayo, Sabela (International Asia Of Law and Money Laundering, 2025)
Mediation is a dispute resolution instrument that emphasizes peace and time efficiency in the judicial process. Based on the regulation of the Supreme Court of the Republic of Indonesia (PERMA) Number 1 of 2016 concerning mediation procedures in court, every civil case must first be resolved through mediation before the examination of the subject matter is carried out. In practice, however, there is still debate as to whether the mediation obligation can be applied at the level of appellate and Cassation remedies. This paper aims to analyze the position and application of mediation obligations in the advanced stages of legal efforts, using normative legal research methods. The results showed that formal mediation is only required at the first examination level, but the spirit of peace on which mediation is based can still be pursued voluntarily at the appeal and Cassation levels. It is necessary to reformulate the regulation so that the opportunities for peace at all stages of the judiciary remain effectively open.